A review of CoSb3-based skutterudite thermoelectric materials - Zhi-Yuan Liu; Jiang-Long Zhu; Xin Tong; Shuo Niu; Wen-Yu Zhao (Journal of Advanced Ceramics, 2020)
Abstract The binary skutterudite CoSb3 is a narrow bandgap semiconductor thermoelectric (TE) material with a relatively flat band structure and excellent electrical performance. However, thermal conductivity is very high because of the covalent bond between Co and Sb, resulting in a very low ZT value. Therefore, researchers have been trying to reduce its thermal conductivity by the different optimization methods. In addition, the synergistic optimization of the electrical and thermal transport parameters is also a key to improve the ZT value of CoSb3 material because the electrical and thermal transport parameters of TE materials are closely related to each other by the band structure and scattering mechanism. This review summarizes the main research progress in recent years to reduce the thermal conductivity of CoSb3-based materials at atomic-molecular scale and nano-mesoscopic scale. We also provide a simple summary of achievements made in recent studies on the non-equilibrium preparation technologies of CoSb3-based materials and synergistic optimization of the electrical and thermal transport parameters. In addition, the research progress of CoSb3-based TE devices in recent years is also briefly discussed.